Analysts' dividend forecasts, portfolio selection, and market risk premia - Wolfgang Breuer; Franziska Feilke; Marc Gürtler (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2007)
The most relevant practical impediment to an application of the Markowitz portfolio selection approach is the problem of estimating return moments, in particular return expectations. We analyze the consequences of using return estimates implied by analysts' dividend forecasts under the explicit notion of taxes and non-flat term structures of interest rates and achieve quite good performance results. As a by-product, these results cast some doubt upon the adequacy of estimating market risk premia with implied returns, because estimation techniques with good performance results are hardly suited to describe market expectations.
Keywords: G11; G12; G14; 330; analysts' forecasts; CAPM; implied returns; market risk premium; portfolio optimization; return estimation